2015
DOI: 10.1002/pola.27522
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the synthesis and impact of end-functional poly(3-hexylthiophene)

Abstract: In recent years, end-functional poly(3-hexylthiophene) (P3HT) has proven to be instrumental in the continued development and innovation within the broad conjugated polymer arena, enabling a variety of applications, particularly in organic electronics. The availability of P3HT with controlled molecular weights, low polydispersity, and importantly, a wide range of reactive end-groups not only serves as a key building block for the preparation of conjugated block copolymers but also facilitates the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 126 publications
0
45
0
Order By: Relevance
“…This short review aims to give a concise summary of polymers with side-chain thiophene-based functionalities, which can be prepared either by controlled polymerization techniques (e.g., ATRP, ROMP, and RAFT) or postpolymerization modification, and to introduce their properties and applications based on some recent or well-representative examples, which includes flexible polymer precursors to conjugated polymers, light-emitting polymeric materials as active components in electroluminescent devices, light-absorbing polymeric materials as active layers in photovoltaic cells, self-assembling amphiphilic block copolymers as functional nanomaterials, surface modification for novel hybrid nanocomposites, etc. Numerous reviews on main-chain thiophene-containing polymers can be found elsewhere [9,11,15,27,28]. This review will be limited to non-conjugated polymers with thiophene-based oligomers as pendant groups.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…This short review aims to give a concise summary of polymers with side-chain thiophene-based functionalities, which can be prepared either by controlled polymerization techniques (e.g., ATRP, ROMP, and RAFT) or postpolymerization modification, and to introduce their properties and applications based on some recent or well-representative examples, which includes flexible polymer precursors to conjugated polymers, light-emitting polymeric materials as active components in electroluminescent devices, light-absorbing polymeric materials as active layers in photovoltaic cells, self-assembling amphiphilic block copolymers as functional nanomaterials, surface modification for novel hybrid nanocomposites, etc. Numerous reviews on main-chain thiophene-containing polymers can be found elsewhere [9,11,15,27,28]. This review will be limited to non-conjugated polymers with thiophene-based oligomers as pendant groups.…”
Section: Introductionmentioning
confidence: 98%
“…Among thiophene-based polymeric materials, thiophene moieties are generally placed in the main-chain architecture. For example, poly(3-hexylthiophene) (P3HT) and their derivatives are one series of the most developed main-chain thiophene-based polymeric materials, which show very promising optoelectronic properties and great potential in OFET and OPV applications [11,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 If the halogen-metal exchange reaction is incomplete or the excess amount of RMgCl is used, non-uniform polymer terminal structures M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 are validated by the matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectra. 13 There are three methodologies to introduce the functional group at the chain termini of P3HT as highlighted by Hawker et al 14 Instead of Ni(dppp)Cl 2 (dppp=1,3-bis(diphenylphosphino)propane) complex originally developed, the application of ArNiXL complexes as the initiator facilitate the introduction of the Ar group at the initiating end of P3HT. Although there are many reports to prepare such kind of external nickel initiators, the universal and easy to handle protocol is still under investigating.…”
Section: Introductionmentioning
confidence: 99%
“…There are generally two approaches to synthesis of the above block copolymers. One is to use P3HTs end‐modified with functional group(s) as macroinitiators for subsequent polymerization of the second monomer. For example, Stefan and co‐workers prepared P3HT‐ b ‐poly(2‐ethyl‐2‐oxazoline) by using trifluoromethanesulfonate‐functionalized P3HT as a macroinitiator for the cationic ring‐opening polymerization of 2‐ethyl‐2‐oxazoline.…”
Section: Introductionmentioning
confidence: 99%